ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN PENGRAJIN SANGGAH DI DESA TARO KECAMATAN TEGALLALANG KABUPATEN GIANYAR - Prananjaya, I Gusti Ngurah Yuda Iswara; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2023)
This research aims to analyze the relationship between the variables of capital, raw materials, and labor as independent variables on production as a mediating variable, and income as the dependent variable in the handicraft SMEs of Sanggah in Taro Village, Tegallalang Sub-district, using Path Analysis. The study was conducted on 63 Sanggah craftsmen in Taro Village, Tegallalang Sub-district, Gianyar Regency. Data collection for this research was done through interviews and questionnaires. The results of this study indicate that the production variable is able to mediate the influence of capital, raw materials, and labor on the income of Sanggah craftsmen in Taro Village, Tegallalang Sub-district, Gianyar Regency. In other words, if there is an increase in the independent variables, there will be an increase in income through the mediation of the production variable. keyword : Production; Revenue; Sanggah craftsmen; Path Analysis